Interleukin-4 promotes human CD8 T cell expression of CCR7. - Seneviratne, S; Black, A; Jones, L; di Gleria, K; Bailey, A; Ogg, G (2007)
Despite strong evidence supporting a pathway of human T cell differentiation characterized by changes in the expression of CCR7, CD28, CD27 and CD62L, few studies have addressed the mechanisms of pathway regulation. Cutaneous lymphocyte-associated antigen (CLA)-positive skin-homing CD8(+) T cells expressed significantly elevated levels of activation markers compared with CLA(-) CD8(+) T cells in individuals (n = 27) with cutaneous atopic disease. Despite such an activated phenotype, CLA(+) T cells expressed significantly higher levels of CCR7 than a CLA(-) T cell subset. Interleukin (IL)-4 was found to dramatically promote CCR7 expression by antigen-specific CD8(+) cells. Furthermore, skin-homing CD8(+) T cells from individuals with severe disease produced significantly less IL-10 than those derived from mildly affected atopic subjects. Thus in a T-helper 2 dominated disease, tissue-specific CD8(+) T cells show altered CCR7 expression and cytokine production, which may contribute to continued lymph node homing, antigen presentation and disease. IL-4 promotes expression of CCR7, a marker linked to existing models of CD8(+) T cell differentiation.